Olga Katsiardi-Hering, Anastasia Papadia-Lala, Katerina Nikolaou and Vangelis Karamanolakis (eds.), Έλλην, Ρωμηός, Γραικός: Συλλογικοί προσδιορισμοί και ταυτότητες [Hellene, Romios, Greek: Collective designations and identities] - Chrissidis, Nikolaos (The Historical Review/La Revue Historique, 2021)
Review of:Olga Katsiardi-Hering, Anastasia Papadia-Lala, Katerina Nikolaou and Vangelis Karamanolakis (eds.), Έλλην, Ρωμηός, Γραικός: Συλλογικοί προσδιορισμοί και ταυτότητες [Hellene, Romios, Greek: Collective designations and identities]